EFFECT OF ALLOXAN - INDUCED DIABETES ON SERUM ELECTROLYTES AND LIPIDS IN RABBITS - Shafique, Muhammad; Khan, Misbahul Ain; Chughtai, Amjad M.; Kahloon, Akbar Ali; Khan, Iqbal Ahmad (Journal of Ayub Medical College Abbottabad, 1992)
ABSTRACT: Effect of alloxan on scrum glucose, electrolytes and lipids was observed in 20 induceddiabetic rabbits. Thirteen days after alloxan administration sufficient hyperglycemia was detected and the serum levels of magnesium and sodium were lower significantly. Out of 20, eight Rabbits (40%) developed marked hypomagnesemia and hyponatremia which were inversely associated with the degree of hyperglycemia. Serum HDL-cholesterol was also decreased and triglycerides increased statistically. However, the difference in the mean values of total cholesterol, calcium and potassium were found to be non-significant after alloxan injection.